Synthesis And Characterisations Of Titanium Dioxide (Tio2)/ Cellulose Biochar Composites For Photocatalytic Degradation Of Congo Red - Wong, Wai Teck (2020)
In this research, cellulose biochar/ titanium dioxide (TiO2) composites were synthesised using sol-gel method and being calcined at different temperature for photocatalytic degradation of Congo Red. The characteristics of cellulose biochar/ TiO2 composites were studied using the X-ray diffraction (XRD), scanning electron microscopy- energy dispersive X-ray analysis (SEM-EDX), Fourier transformed infrared (FTIR) spectroscopy, Thermogravimetric analysis (TGA) analyses and zeta potential analyses. Anatase and rutile phases of TiO2 had been detached and distributed on the cellulose biochar surface of the composite materials. EDX results showed mainly of carbon, oxygen and titanium elements. The zero charge point of cellulose biochar/ TiO2-700 was pH 5.1. A few operating parametersstudiessuch astype of catalysts, catalyst dosage, solution pH, potassium peroxymonosulfate (PMS) dosage, dye concentration, solution temperature and type of organic dyes to determine the optimum conditions for photocatalytic degradation of organic dye. It was found that increasing the calcination temperature of cellulose biochar/ TiO2 composites increased the photocatalytic degradation efficiency of Congo Red before it reached the optimum point and decreased beyond the calcination temperature. The optimum conditions for the photocatalytic degradation of Congo Red were 0.5 g/L of cellulose biochar/ TiO2-700 with 0.3 mM of PMS used to treat an initial dye concentration of 10 mg/L under 30 °C and solution pH 5. Under these conditions, the degradation efficiency of Congo Red was 100 % in 30 minutes whereas the COD removal efficiency was 84.5 % in 120 minutes. The reusability was also studied and photocatalytic degradation of Congo Red was followed pseudo second-order kinetics with activation energy (